Good Food, Good Mood: Perspectives on the Relationship Between Nutrition and Mental Health With Division I Collegiate Athletic Programs - McCabe, Emma M.; Ketcham, Caroline J.; Hall, Eric E. (Frontiers in Sports and Active Living, 2021)
Research has shown a strong relationship between nutrition and mental health. Packed schedules and little rest time may make student-athletes more susceptible to mental health issues than the general population, but few athletes are fully aware of the effects that nutrition can have on their mental health. While collegiate athletic programs are beginning to recognize the individual contributions of nutrition and mental health to performance and are hiring sport dietitians and psychologists for their athletes, it is unclear whether these topics are ever discussed within the same context. The goal of this study was to understand the perspectives of different athletic personnel on the relationship between nutrition and mental health. 17 athletic personnel (11 Female, 6 Male) from 6 NCAA Division I universities were recruited for a 30–45-min semi-structured WebEx interview. Participants included athletic trainers, coaches, dietitians, sport psychologists, strength and conditioning coaches, and sports medicine physicians. Participants were asked questions about their educational backgrounds, resources, and perspectives on the integration of nutrition and mental health in their programs. Transcribed responses were sorted into four themes: (1) Resources, (2) Education, (3) Department Integration or Collaboration, and (4) Student and Coach Engagement. All participants reported a need for greater monetary resources and staffing. Around 59% of the participants felt they had little more than general or personal interest-level knowledge on topics pertaining to nutrition or mental health, with the exception of sports dietitians or psychologists. Each school varied in the degree to which their athletic staff regularly communicated about their work and athlete health statuses. Athletes were reportedly more or less likely to utilize the resources provided depending on coach attitudes toward nutrition or mental health. Regardless of size, reputation and annual spending, each university was reported to be in the early stages of integrating nutrition and mental health programs into their existing athletic departments. Implications of this work may be to help schools plan for ways to reallocate funding for nutrition or mental health programming.